The Impacts of Board Diversity on CSR Performance–based on the UK Corporate Governance Code 2024 - Song, Baijia (Journal of Global Economy, Business and Finance, 2024)
With the process of globalization and the rapid development of companies, corporate social responsibility (CSR) has received increasing attention. Based on triple bottom line (TBL), companies must not only achieve economic progress, but also be expected to fulfill CSR, making contributions to the natural environment and the community prosperity. As a vital part of the company management, the composition of the board of directors has always been a focus of attention. There are many standards and indicators for corporate governance (CG), including the UK Corporate Governance Code 2024, which will be utilized as the theoretical basis for this research. This research focuses on the principles of diversity of the board, and their impacts on CSR. Surrounded this topic, the latest opinions published in recent years will be groped and analyzed.